Reference point formation-does the market whisper in the background? - Wang, Tianyang, author; Villupuram, Sriram V., author; Schwebach, Robert G., author; 2018 FMA Annual Meeting, publisher (Colorado State University. Libraries, 2018)
Experimental studies in behavioral finance historically have confirmed that subjects are highly influenced by reference points when making economic decisions. A recent study by Baucells, Weber and Welfens (2011) analyzed the dynamics of reference price formation using experimental methods with subjects forming reference prices for stocks based on observed price sequences. Their study helps to clarify behavioral effects of past prices on reference price formation but it does not consider contextual information. We extend the BWW study by adding market price information as background to the experiment, and we investigate how this additional information affects reference point formation and updating. Our overarching hypothesis is that if the market background information has no impact then it should not alter the results of BWW; otherwise, the additional market information should be an explanatory variable for the reference point. Our results confirm the hypothesis that market information matters. We also investigate the impact of pessimism and optimism on reference prices by the combining the BWW framework with a model of disappointment aversion and anticipatory feelings developed by Gollier and Muerman (2010). Our study fills a void in the literature by providing new evidence on the impact of contextual market information on reference point formation in an investment setting.
Presented at FMA 2018 Annual Meeting, San Diego, CA.
Keywords: behavioral finance; reference-point formation; reference-dependent preferences